2013
DOI: 10.5588/ijtld.12.0385
|View full text |Cite
|
Sign up to set email alerts
|

Burden of tuberculosis in indigenous peoples globally: a systematic review [Review article]

Abstract: SUMMARY BACKGROUND The burden of tuberculosis (TB) in the estimated 370 million indigenous peoples worldwide is unknown. OBJECTIVE To conduct a literature review to summarize the TB burden in indigenous peoples, identify gaps in current knowledge, and provide the foundation for a research agenda prioritizing indigenous health within TB control. METHODS A systematic literature review identified articles published between January 1990 and November 2011 quantifying TB disease burden in indigenous populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 54 publications
5
80
0
4
Order By: Relevance
“…A review of published data on TB disease burden in indigenous populations worldwide found that, in most cases, indigenous populations have higher rates of active TB disease than nonindigenous populations [1,2]. These findings are consistent with growing evidence on health disparities between indigenous and nonindigenous people worldwide; across regions, macrolinguistic families, and countries, disease burden and disability rates are higher among the former when compared to their most underprivileged neighbors [2][3][4].…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…A review of published data on TB disease burden in indigenous populations worldwide found that, in most cases, indigenous populations have higher rates of active TB disease than nonindigenous populations [1,2]. These findings are consistent with growing evidence on health disparities between indigenous and nonindigenous people worldwide; across regions, macrolinguistic families, and countries, disease burden and disability rates are higher among the former when compared to their most underprivileged neighbors [2][3][4].…”
Section: Introductionsupporting
confidence: 72%
“…The TB burden in indigenous communities of the Chaco region fits well within the range of variation in indigenous TB burden worldwide and further supports evidence that indigenous people generally suffer greater disease burden than nonindigenous people [1]. When compared with other South American indigenous groups (Figure 1), the burden of disease in Chacoan indigenous groups is lower than that experienced by their indigenous neighbors.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Tal estudo revelou que a carga da tuberculose é elevada e desproporcional, com grande variação entre grupos e regiões. Os grupos indígenas com maior carga da doença estão localizados em pequenas regiões da América Latina 28 .…”
Section: Discussionunclassified
“…Indigenous communities in many high-income countries have substantially higher rates of tuberculosis than the non-indigenous population (9) and rates of tuberculosis are particularly high amongst the Inuit in the Canadian Arctic regions (10). Although socioeconomic factors are thought to be important contributors, the reasons for this remain unclear, making it difficult to target interventions to reduce this disease burden.…”
mentioning
confidence: 99%